TEOLOGI BENCANA KAUM PESANTREN - Tolchah, Moch (KARSA: Journal of Social and Islamic Culture, 2015)
The construction of theological thought of Islamic scholars about disaster in East Java is based on the dialogue process which is based on the text (the doctrine of theology) and context (a variety of catastrophic events). The scholar thought dia-lectically involves three momentums at once, the moment of internalization, ex-ternalization, and objectification. This cycle can be seen from the understanding of the resource person which is based on the doctrine of theology and catas-trophic events. The dialectics of text and context eventually lead to the concerns of the scholars. This study concludes that in the view of the primary sources, the disaster is interpreted in three categories, namely as mushîbah (trials), imtihân (warning/test), and 'adzab (torture) of God as prime cause for humanity in hablun min Allah (relationship/worship with Allah), hablun min al al-nâs (relation-ship/interact with human), and hablun min al-'âlam (relationship/maintain with universe). Generally, this theological view can not be separated from mainstream theology, the theology of the Ash'arite which is the mainstream ideology of Ahlussunnah wal Jama'ah followers. Polarization of views and interpretations of the Islamic scholars in East Java in Berger’s constructivism theory gives rise typology of scholar thought; conservative, moderate and progressive thought.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.729